Penatalaksanaan Periodontitis Kronik Pada Penderita Diabetes Mellitus - Victoria Dewanti Arifiana; Nabila Prandita (Fakultas Kedokteran Gigi Universitas Jember, 2019)
Diabetes mellitus (DM) is a metabolic disorder that can occur genetically and clinically, including heterogeneous with manifestations in the form of loss of tolerance for carbohydrates. One of the complications of diabetes mellitus in the field of dentistry is oral diabetes including dry mouth, gingivitis, calculus, alveolar bone resorption, and periodontitis. Periodontitis is an inflammatory disease of the tooth supporting tissue caused by a particular group of microorganisms usually derived from dental plaque which can result in the progressive destruction of the periodontal connective tissue and alveolar bone with pocket formation, recession, or both. This case report is to study the management of chronic periodontitis in DM sufferers. The 52-year-old female patient came with complaints of missing and perforated back teeth wanting treatment. The patient has a history of diabetes. The incidence of periodontitis in DM has a greater incidence rate, therefore the existence of glycemic control plays an important role in preventing any deterioration.